Economic reforms for the poor - Gango padhyay, Shubhashis; Wadhwa, Wilima (Delhi Konark, 2000)
The book entitled `Economic reforms for the poor`gives a fresh look at the globalisation and liberalisation process in a strategy that will make reforms process bring to benefit,wherever possible,to the poor population of India.It highlights some of the m
Keywords: Poor; Agriculture-Economic aspects; Employment (Economic theory); Education-Economic aspects